2023
DOI: 10.1073/pnas.2301258120
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily diverse origins of deformed wing viruses in western honey bees

Abstract: Novel transmission routes can allow infectious diseases to spread, often with devastating consequences. Ectoparasitic varroa mites vector a diversity of RNA viruses, having switched hosts from the eastern to western honey bees ( Apis cerana to Apis mellifera ). They provide an opportunity to explore how novel transmission routes shape disease epidemiology. As the principal driver of the spread of deformed wing viruses (mainly DWV-A and DWV-B), varroa infestation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Similarly, Hsu et al (2019) report aggressive behavior in the ant Anoplolepis gracilipes being shaped by viral disease transmission triggered by a dicistrovirus. In bees, iflaviruses such as Sacbrood virus and Deformed wing virus (DWV) increase aggressiveness in infected colonies of Apis cerana (Hasegawa et al, 2023) and A. mellifera (Fujiyuki et al, 2004; Terio et al, 2008, but see Rortais et al 2006). Thus, the viruses that were highly expressed in very active A. octoarticulatus bodyguards may also be manipulating the behavior of their ant hosts, with potential consequences for both their own transmission and for the degree of protection afforded by the ants.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Hsu et al (2019) report aggressive behavior in the ant Anoplolepis gracilipes being shaped by viral disease transmission triggered by a dicistrovirus. In bees, iflaviruses such as Sacbrood virus and Deformed wing virus (DWV) increase aggressiveness in infected colonies of Apis cerana (Hasegawa et al, 2023) and A. mellifera (Fujiyuki et al, 2004; Terio et al, 2008, but see Rortais et al 2006). Thus, the viruses that were highly expressed in very active A. octoarticulatus bodyguards may also be manipulating the behavior of their ant hosts, with potential consequences for both their own transmission and for the degree of protection afforded by the ants.…”
Section: Discussionmentioning
confidence: 99%
“…The post-vector-invasion DWV-epidemic in New Zealand and Hawai’i consisted of DWV-A [ 21 , 27 ]. While this variant globally spread in parallel with varroa over the last century [ 8 , 18 ], the recently emerged DWV-B [ 25 ] has rapidly gained in prevalence in the UK and the US, potentially replacing the older DWV-A [ 37 ]. For instance, in the US, DWV-B increased from 3% prevalence in 2010 to 66% in 2016 [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The re-emergence of DWV and its global spread followed varroa's host switch to western honeybees [8,18]. In addition, there are multiple other honeybee viral pathogens that are vectored by varroa [19] and that have also been shown to increase in prevalence in the presence of this vector, such as acute bee paralysis virus (ABPV), black queen cell virus (BQCV) and slow bee paralysis virus (SBPV) [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that the entire DWV-B genome is under exceptionally strong purifying selection, which minimizes changes to both the nucleic acid and amino acid sequences. Others have found that DWV-A and DWV-B diverged approximately 308 years ago, predating the documented Varroa host switches [ 61 ]. Given the low substitution rate observed here, this estimate appears plausible.…”
Section: Discussionmentioning
confidence: 99%